(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
The thermal decomposition reaction of benzaldehyde diperoxide (DFT; 0.001 mol L-1) in nitromethane solution studied in the temperature range of 130.0-166.0 °C, follows a first-order kinetic law up to at least 60% DFT conversion. The organic products observed were benzaldheyde and benzoic acid. A stepwise mechanism of decomposition was proposed where the first step is the homolytic unimolecular rupture of the O-O bond. The activation enthalpy and activation entropy for DFT in nitromethane were calculated (DH# = 106.3 ± 1.0 kJ mol-1 and DS# = -58.6 ± 1.1 J mol-1K-1) and compared with those obtained in other solvents to evaluate the solvent effect.